2014
DOI: 10.1111/tbj.12303
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Survivin in Breast Cancer: Meta-analysis

Abstract: Survivin, an inhibitor of apoptosis protein, is a potentially prognostic factor and therapeutic target in breast carcinoma, but no consensus exists based on heterogeneous data. The aim of this present study is to clarify the prognostic relevance of survivin in breast cancer patients. Relevant articles were screened in PubMed and EMBASE databases. Patients' clinical characteristics, overall survival (OS), disease/recurrence-free survival (DFS/RFS) and positive expressed survivin rates were extracted for further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Adida et al reported that survivin expression in neuroblastoma correlated with unfavorable histology and aggressive and disseminated disease [15]. In colorectal cancer and breast cancer, patients with surviving-positive tumors had a decreased apoptotic index and worse survival rates than those with survivin-negative tumors [17, 27]. In addition, survivin expression was correlated with poor prognosis in esophageal cancer and non-small cell lung cancer [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Adida et al reported that survivin expression in neuroblastoma correlated with unfavorable histology and aggressive and disseminated disease [15]. In colorectal cancer and breast cancer, patients with surviving-positive tumors had a decreased apoptotic index and worse survival rates than those with survivin-negative tumors [17, 27]. In addition, survivin expression was correlated with poor prognosis in esophageal cancer and non-small cell lung cancer [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis was conducted to find relationships between positive survivin expression and poor overall survival in breast cancer and lymph node metastasis patients. Overexpression of survivin indicated a significantly higher risk of recurrence and reduced overall survival 59,60…”
Section: Embasementioning
confidence: 99%
“…Positive expression of survivin in breast cancer predicted a significantly higher risk of disease recurrence and is shown to be associated with lymph node metastasis (P value = 0.01) [16]. The rate of survivin expression seems to correlate with the sensitivity of survivin detection methods.…”
Section: Survivinin Breast Cancermentioning
confidence: 96%